The miRNA–immune axis in bladder cancer: systematic evidence for a new era of immunotherapy precision - Dulf, Daniel-Vasile; Ravegnini, Gloria; Giorgi, Federico Manuel; Burnar, Anamaria Larisa; Gorini, Francesca; De Leo, Antonio; Luţichievici, Harisa; Opriţa, Constantin-Lucian; Todiruţ, Cezar-Nicolae; Ciuleanu, Tudor-Eliade; Coadă, Camelia Alexandra (Frontiers in Immunology, 2025)
IntroductionBladder cancer (BC) is a complex disease with patients showing widely variable responses to treatment. While immunotherapy has recently emerged as a promising alternative to the standard platinum-based chemotherapy, especially for platinum-resistant tumors, clinicians still lack reliable biomarkers to predict which patients will truly benefit from immunotherapy.AimThis systematic review aimed to explore whether miRNAs could help decode the immune landscape of BC and serve as predictive biomarkers for immunotherapy response.MethodsA total of 3,272 articles were systematically screened on medical databases and narrowed down to 37 studies that examined the relationship between miRNAs, immune cell infiltration, and patient outcomes in BC. To further strengthen and validate our findings, we analyzed large-scale genomic data from The Cancer Genome Atlas (TCGA-BLCA).ResultsA total of 104 different miRNAs appeared to shape the BC immune microenvironment. Some studies also linked miRNA expression with clinical outcomes such as BCG therapy response and prognosis, while others dissected the molecular pathways. Further analyses established miR-155, miR-142, and miR-146b as key factors for CD4+ memory T-cell and M1 macrophage infiltration. Notably, 49 miRNAs showed stage-specific expression differences in TCGA data, with 25 of them also significantly associated with progression-free interval or overall survival.ConclusionmiRNAs are emerging as powerful regulators of the immune microenvironment of BC. However, despite growing evidence, to date, no studies have directly explored miRNA profiles in driving immunotherapeutic decisions. Our findings highlight the need for prospective studies to translate these molecular insights into personalized treatment strategies.